Human African trypanosomiasis - Welburn, Susan (Henry Stewart Talks, 2021)
Introduction to Human African Trypanosomiasis (HAT, Sleeping Sickness), Two types of HAT, Stages of Sleeping Sickness, History and geography of HAT epidemics, Active medical surveillance of HAT, The role of domestic animals in HAT infection, Control methods and management